Real‐world evaluation of the impact of two anti‐SARS‐CoV‐2 monoclonal antibody regimens on COVID‐19 hospitalizations in older adults. Issue 6 (3rd March 2022) - Sobolewski, Kristine A.; Smoke, Steven M.; Brophy, Alison; Vassallo, Andrew V.; Chen, Brandon; Hilden, Patrick; Patterson, Rebecca; Pittiglio, Marina; Raja, Karan; Handler, Eric; Freer, Christopher
Abstract: Evidence from clinical trials suggest anti‐SARS‐CoV‐2 monoclonal antibodies (mABs) may reduce coronavirus disease 2019 (COVID‐19)‐related hospitalizations. The purpose of this study was to assess the real‐world impact of mAB administration on COVID‐19 hospitalization among patients 65 years or older. This was a retrospective, propensity‐matched cohort study that included patients aged 65 years and older who presented to the emergency department (ED) within 10 days of symptom onset of mild to moderate COVID‐19 infection. Outcomes were compared between those who did and did not receive mAB therapy. The primary endpoint was the rate of hospitalization for COVID‐19 within 30 days of index ED visit. A total of 137 patients receiving mABs were matched to 137 controls. Hospitalization occurred in 2.9% of mAB‐treated patients compared to 14.6% of patients of the standard of care (SOC) arm (odds ratio: 0.20 [95% CI: 0.07–0.59]). There were zero intubations and zero deaths compared to 3 (2.2%) and 2 (1.5%) in the SOC group. Among the 223 patients receiving mAB in the overall cohort, adverse drug events occurred in 10 (4.5%). Treatment with mAB therapy for mild to moderate COVID‐19 was associated with a substantially reduced risk of hospitalization among patients at least 65 years of age.